D. Graham J. Shipley, The Early Hellenistic Peloponnese: Politics, Economies, and Networks 338-197 BC. pp. xxxii+355, 1 ill., 9 maps, 7 tables. 2018. Cambridge: Cambridge University Press. ISBN 2018978-0-521-87369-7, hardback 120. - Pettegrew, David (Journal of Greek Archaeology, 2020)
The ‘decline’ of the polis in the late Classical and early Hellenistic periods numbers among the stock elements of historical narratives of ancient Greece. In the conventional rendition baked into old textbook descriptions of Greek civilization, the aftermath of the Peloponnesian War marked the end of a golden age as city-states devolved into a downward cycle of power play, hegemonic contest, and warfare that ended only with the conquests of Philip II and Alexander. The polis thereafter lost its autonomy, political directive, and ideological essence. As one popular textbook of western civilization put it recently: ‘With the advent of Macedonian control, once-independent poleis became subject cities whose proud political traditions were no longer relevant.’ This picture of decline, decay, and irrelevance remains common today despite a range of recent scholarship reappraising the early Hellenistic period in Greece.